Clinical application of immunogenic cell death inducers in cancer immunotherapy: turning cold tumors hot - Han, Yiman; Tian, Xin; Zhai, Jiaqi; Zhang, Zhenyong (Frontiers in Cell and Developmental Biology, 2024)
Immunotherapy has emerged as a promising cancer treatment option in recent years. In immune “hot” tumors, characterized by abundant immune cell infiltration, immunotherapy can improve patients’ prognosis by activating the function of immune cells. By contrast, immune “cold” tumors are often less sensitive to immunotherapy owing to low immunogenicity of tumor cells, an immune inhibitory tumor microenvironment, and a series of immune-escape mechanisms. Immunogenic cell death (ICD) is a promising cellular process to facilitate the transformation of immune “cold” tumors to immune “hot” tumors by eliciting innate and adaptive immune responses through the release of (or exposure to) damage-related molecular patterns. Accumulating evidence suggests that various traditional therapies can induce ICD, including chemotherapy, targeted therapy, radiotherapy, and photodynamic therapy. In this review, we summarize the biological mechanisms and hallmarks of ICD and introduce some newly discovered and technologically innovative inducers that activate the immune system at the molecular level. Furthermore, we also discuss the clinical applications of combing ICD inducers with cancer immunotherapy. This review will provide valuable insights into the future development of ICD-related combination therapeutics and potential management for “cold” tumors.